Comparative Analysis of International and Legal Documents on Tourism and Counteraction to the Threat of International Terrorism - ALEYNIKOV, Boris N.; SHAPIROVA, Railya R.; KADYROV, Marsel A.; PONOMAREV, Andrey A. (Journal of Environmental Management and Tourism, 2018)
International terrorism is the deliberate use or threat of violence against civilians in order to achieve political goals. Terrorist acts, local or international, cause immediate human, economic and psychological consequences of varying intensity. However, their influence does not stop there, because most of the indirect effects, which are widely diversified by types of activity, regions, countries and time are observed. The problem of international regulatory security provision of international tourism is one of the most acute and at the same time complex, but the solution of which must be found without delay due to terrorist attacks on tourist centers in 2014-2016. As a result of the research with the help of comparative analysis and problem-chronological method it was proved that in international law there is no modern single standard adopted in the framework of the World Tourism Organization to prevent terrorist threats to international tourism and tourists. For the first time, the concept of such a document was proposed. The approaches to understanding not only the essence of the terrorist threat as anthropological factors but also the economic basis is comprehensively defined in the study.